2010
DOI: 10.1111/j.1364-3703.2010.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of plant immunity

Abstract: In eukaryotic genomes, gene expression and DNA recombination are affected by structural chromatin traits. Chromatin structure is shaped by the activity of enzymes that either introduce covalent modifications in DNA and histone proteins or use energy from ATP to disrupt histone-DNA interactions. The genomic 'marks' that are generated by covalent modifications of histones and DNA, or by the deposition of histone variants, are susceptible to being altered in response to stress. Recent evidence has suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(96 citation statements)
references
References 168 publications
1
94
0
Order By: Relevance
“…Although the molecular mechanisms of same-generation priming have recently started to be better understood (for review, see Conrath, 2011), the molecular details underlying transgenerational priming are still under study. However, recent groups have demonstrated that epigenetic mechanisms play a role in plant defense and several review articles comment on the possible involvement of epigenetic mechanisms in transgenerational phenomena (Chinnusamy and Zhu, 2009;Alvarez et al, 2010;Sano, 2010). Histone modifications are examples of epigenetic mechanisms; indeed, such modifications in the promoters of defense genes have been shown to correlate with transgenerational induced resistance in Arabidopsis against abiotic (Boyko et al, 2010) and biotic stresses (Luna et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms of same-generation priming have recently started to be better understood (for review, see Conrath, 2011), the molecular details underlying transgenerational priming are still under study. However, recent groups have demonstrated that epigenetic mechanisms play a role in plant defense and several review articles comment on the possible involvement of epigenetic mechanisms in transgenerational phenomena (Chinnusamy and Zhu, 2009;Alvarez et al, 2010;Sano, 2010). Histone modifications are examples of epigenetic mechanisms; indeed, such modifications in the promoters of defense genes have been shown to correlate with transgenerational induced resistance in Arabidopsis against abiotic (Boyko et al, 2010) and biotic stresses (Luna et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Hence a quality check up for true to type planting material at an early stage of development is considered to be very useful in plant tissue culture (Zilberman and Henikoff 2007). Although molecular basis of genetic variations are now becoming apparent that involves transcription, transposable element, chromosomal rearrangement, gene amplification, gene mutation (Alvarez et al 2010). Molecular markers serve as an important tool to check the genetic uniformity and true to type nature of micropropagated plants.…”
Section: Introductionmentioning
confidence: 99%
“…Posttranslational modifications at the N-terminal tail of histone H3 can influence defense-related gene expression (van den Burg and Takken, 2009;Alvarez et al, 2010). Because these chromatin modifications can have long-lasting impacts on plant gene expression (Vaillant and Paszkowski, 2007), we investigated whether the altered responsiveness of PR-1 and PDF1.2 in P 1 plants is associated with changes in chromatin structure at the promoter regions of these genes.…”
Section: Transgenerational Chromatin Modifications At Defense Gene Prmentioning
confidence: 99%
“…The mechanisms of long-lasting maintenance of SAR, on the other hand, have remained less intensely studied. Recent studies have begun to analyze how epigenetic regulatory mechanisms, such as DNA methylation and chromatin remodeling, can have long-lasting impacts on gene expression and plant immunity (Bruce et al, 2007;van den Burg and Takken, 2009;Alvarez et al, 2010).…”
mentioning
confidence: 99%